Management Issues of Heritage Tourism and Recommendations for Better Heritage Preservation in Viet Nam - Kieu, Tien (Tạp chí Khoa học HUFLIT, 2023)
Heritage sites are the most valuable and important resources that need to be conserved properly. Nowadays, many heritage locations have been transformed into tourism products and have become a key tourism economic tool in some countries. Viet Nam has plenty of heritage spots and many of them are recognized as UNESCO World Heritage sites. The increasing number of tourists travel to Viet Nam to visit these places, so heritage tourism emerges as one of the leading tourism activities to bring economic, social and cultural benefits to the country in general as well as local authorities and residents in particular. However, increased number of visits to these scenes result in degradation. Heritage management plays a decisive role in managing visitors to historic places with the purpose of enhancing the visitors’ appreciation and experience, but failure to embrace diverse heritage management practices causes different challenges. This paper aims to identify two key benefits of heritage tourism like economic and social cultural ones, find out negative impacts of tourisms on heritage grounds, present management issues on preserving heritages sites in Vietnam and propose some recommendations in the areas of heritage management.